2016
DOI: 10.1038/srep38479
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary behavioral entrainment following circadian rhythm bifurcation in mice

Abstract: The mammalian circadian timing system uses light to synchronize endogenously generated rhythms with the environmental day. Entrainment to schedules that deviate significantly from 24 h (T24) has been viewed as unlikely because the circadian pacemaker appears capable only of small, incremental responses to brief light exposures. Challenging this view, we demonstrate that simple manipulations of light alone induce extreme plasticity in the circadian system of mice. Firstly, exposure to dim nocturnal illumination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 27 publications
6
52
2
Order By: Relevance
“…Each of these animals remained very well-adapted to the light-dark cycles throughout the experiment, as evident from little activity in the light, and no visible free-running components. A measure of equality of division of activity between alternate scotophases in LDLD, the Bifurcation Symmetry Index (BSI; [17]), indicated that mice were well-bifurcated during the first phase of the experiment (0.71 ± 0.08 and 0.56 ± 0.11 for females and males respectively; t(10.0) = 1.14; p = 0.28). A complementary measure that quantifies behavioral adaptation in T-cycles, Entrainment Quotient (EQ; [17]), showed that mice were likewise well-adapted in T30 baseline (0.96 ± 0.02 and 0.83 ± 0.06 for females and males) and T36 baseline (0.97 ± 0.01 and 0.91 ± 0.05 females and males).…”
Section: Study 1/jitter-resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Each of these animals remained very well-adapted to the light-dark cycles throughout the experiment, as evident from little activity in the light, and no visible free-running components. A measure of equality of division of activity between alternate scotophases in LDLD, the Bifurcation Symmetry Index (BSI; [17]), indicated that mice were well-bifurcated during the first phase of the experiment (0.71 ± 0.08 and 0.56 ± 0.11 for females and males respectively; t(10.0) = 1.14; p = 0.28). A complementary measure that quantifies behavioral adaptation in T-cycles, Entrainment Quotient (EQ; [17]), showed that mice were likewise well-adapted in T30 baseline (0.96 ± 0.02 and 0.83 ± 0.06 for females and males) and T36 baseline (0.97 ± 0.01 and 0.91 ± 0.05 females and males).…”
Section: Study 1/jitter-resultsmentioning
confidence: 99%
“…A measure of equality of division of activity between alternate scotophases in LDLD, the Bifurcation Symmetry Index (BSI; [17]), indicated that mice were well-bifurcated during the first phase of the experiment (0.71 ± 0.08 and 0.56 ± 0.11 for females and males respectively; t(10.0) = 1.14; p = 0.28). A complementary measure that quantifies behavioral adaptation in T-cycles, Entrainment Quotient (EQ; [17]), showed that mice were likewise well-adapted in T30 baseline (0.96 ± 0.02 and 0.83 ± 0.06 for females and males) and T36 baseline (0.97 ± 0.01 and 0.91 ± 0.05 females and males). Considering data from the two non-24 h conditions, EQ-values were significantly higher in females than males (F(1,28) = 5.93; p < 0.05), but did not differ between T30 and T36 (F(1,28) = 1.32; p = 0.26), and there was no interaction between T-cycle and sex (F(1,28) = 0.77; p = 0.39).…”
Section: Study 1/jitter-resultsmentioning
confidence: 99%
See 3 more Smart Citations